miR-941 as a promising biomarker for acute coronary syndrome - Bai, Ruina (BMC Cardiovasc Disord, 2017)
BACKGROUND: Circulating miRNAs can function as biomarkers for diagnosis, treatment, and prevention of diseases. However, it is unclear whether miRNAs can be used as biomarkers for acute coronary syndrome (ACS). To this end, we applied gene chip technology to analyze miRNA expression in patients with stable angina (SA), non-ST elevation ACS (NSTE-ACS), and ST-segment elevation myocardial infarction (STEMI). METHODS: We enrolled patients with chest pain who underwent diagnostic coronary angiography, including five patients each with SA, NSTE-ACS, or STEMI, and five controls without coronary artery disease (CAD) but with three or more risk factors. After microarray analysis, differential miRNA expression was confirmed by quantitative real-time reverse transcription polymerase chain reaction (qRT-PCR). RESULTS: Compared with those in patients with STEMI, differentially expressed microRNAs in controls and patients with SA or NSTE-ACS were involved in inflammation, protein phosphorylation, and cell adhesion. Pathway analysis showed that differentially expressed miRNAs were related to the mitogen-activated protein kinase signaling, calcium ion pathways, and cell adhesion pathways. Compared with their expression levels in patients with STEMI, miR-941, miR-363-3p, and miR-182-5p were significantly up-regulated (fold-change: 2.0 or more, P < 0.05) in controls and patients with SA or NSTE-ACS. Further, qRT-PCR showed that plasma miR-941 level was elevated in patients with NSTE-ACS or STEMI as compared with that in patients without CAD (fold-change: 1.65 and 2.28, respectively; P < 0.05). Additionally, miR-941 expression was significantly elevated in the STEMI group compared with that in the SA (P < 0.01) and NSTE-ACS groups (P < 0.05). Similarly, miR-941 expression was higher in patients with ACS (NSTE-ACS or STEMI) than in patients without ACS (without CAD or with SA; P < 0.01). There were no significant differences in miR-182-5p and miR-363-3p expression. The areas under the receiver operating characteristic curves were 0.896, 0.808, and 0.781 for patients in the control, SA, and NSTE-ACS groups, respectively, compared with that for patients with STEMI; that for the ACS group compared with the non-ACS group was 0.734. CONCLUSION: miR-941 expression was relatively higher in patients with ACS and STEMI. Thus, miR-941 may be a potential biomarker of ACS or STEMI. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12872-017-0653-8) contains supplementary material, which is available to authorized users.